The concept of compassionate care in nursing: a meta-synthesis - Ali Asghar Khaleghi; Masoud Mohammadi (Nursing and Midwifery Studies)
Background: Compassionate care contributes to improved diagnosis and patient treatment, enhanced quality of care, increased patient satisfaction and reduced workplace tension. Given the diverse interpretations of compassionate care in nursing, this study aims to consolidate the concept of compassionate care in nursing through a meta-synthesis.Methods: The meta-synthesis was conducted between March 2000 and February 2022 in English and Persian. Relevant articles were retrieved from WoS, Medline (PubMed), CINAHL, Psychinfo, ScienceDirect SID, Magiran, Barakat, and Scopus. The search process was conducted using keywords such as nurse, compassion, and compassionate care along with their equivalent terms, including Compassion, Nursing, and Compassionate Care. The findings from different articles were integrated and categorized into common themes, elucidating the concept within each theme. The meta-synthesis method involved searching articles and then explaining the concept based on the opinion of nursing experts.Results: The meta-synthesis, encompassing 14 studies, identified four general categories- ethics, empathy, dutifulness and communication to explain and integrate compassionate care in nursing. In the ethics category, compassionate care emerged as a natural response to pain and suffering as well as a religiously endowed moral virtue. Regarding empathy, compassionate care involves paying attention to patient problems, listening to the patient, understanding the patient, engaging in patient care, and allocating sufficient time. In the dutifulness category, compassionate care encompassed proper nurse preparation, maintaining an open mind, trying to understand the patient, and investing time and energy in the patient. Additionally, in the communication category, compassionate care was characterized by emotional responsiveness, interpersonal communication with the patient and effective communication skills.Conclusion: Based on the results of this study and the explanation of the concept of compassionate care in nursing, this concept is based on the categories of ethics, empathy and conscientiousness. Recognizing its importance in nursing practice, the study clarifies the role of compassionate care in nurses' duties, facilitating its integration into their services and enhancing the overall delivery of care.